Linker‐free, silica‐bound olefin‐metathesis catalysts: applications in heterogeneous catalysis - Cabrera, José; Padilla, Robin; Bru, Miriam; Lindner, Ronald; Kageyama, Takeharu; Wilckens, Kristina Friederike; Rominger, Frank; Limbach, Michael (Chemistry - a European journal, 2012)
Abstract A set of heterogenized olefin?metathesis catalysts, which consisted of Ru complexes with the H2ITap ligand (1,3?bis(2?,6??dimethyl?4?dimethyl aminophenyl)?4,5?dihydroimidazol?2?ylidene) that had been adsorbed onto a silica support, has been prepared. These complexes showed strong binding to the solid support without the need for tethering groups on the complex or functionalized silica. The catalysts were tested in the ring?opening?ring?closing?metathesis (RO?RCM) of cyclooctene (COE) and the self?metathesis of methyl oleate under continuous?flow conditions. The best complexes showed a TON>4000, which surpasses the previously reported materials that were either based on the Grubbs?Hoveyda?II complex on silica or on the classical heterogeneous Re2O7/B2O3 catalyst.